In Vitro Mucoadhesive Features of Gliadin Nanoparticles Containing Thiamine Hydrochloride - Silvia Voci; Agnese Gagliardi; Elena Giuliano; Maria Cristina Salvatici; Antonio Procopio; Donato Cosco (MDPI AG, 2024)
Background: Gliadins have aroused significant interest in the last decade as suitable biomaterials for food and pharmaceutical applications. In particular, the oral route is the preferred method of administration for gliadin-based formulations, due to the affinity of this biomaterial for the gut mucosa. However, up to now, this has been demonstrated only by means of in vivo or ex vivo studies. Methods: This is why, in this study, various in vitro techniques were employed in order to evaluate the ability of polymeric nanoparticles, made up of a commercial grade of the protein and an etheric surfactant, to interact with porcine gastric mucin. The nanosystems were also used for the encapsulation of thiamine hydrochloride, used as a model of a micronutrient. Results: The resulting systems were characterized by a mean diameter of ~160-170 nm, a narrow size distribution when 0.2-0.6 mg/mL of thiamine was used, and an encapsulation efficiency between 30 and 45% of the drug initially employed. The incubation of the gliadin nanosystems with various concentrations of porcine gastric mucin evidenced the ability of the carriers to interact with the mucus glycoprotein, showing a decreased Zeta potential after a 4 h incubation (from ~−30 to −40 mV), while demonstrating that the encapsulation of the drug did not affect its bioadhesive features. Conclusions: Altogether, these data support the conceivable application of gliadin nanoparticles as formulations for the oral administration of bioactive compounds.